Non-coding RNAs and exosomal ncRNAs in colorectal cancer - Yalda Zhoulideh (Egyptian Journal of Medical Human Genetics)
Abstract Colorectal cancer (CRC) is a complex disease with many genetic and epigenetic changes leading to dysregulation of cell signaling pathways. In recent years, increasing attention has been paid to the role of non-coding RNA (ncRNA) and exogenous ncRNA in the development and progression of CRC. ncRNAs play an essential role in the regulation of gene expression and cell function, and dysregulation of ncRNA expression is associated with the onset and progression of CRC. In this review, we discuss the molecular pathways involved in CRC and the emerging roles of ncRNAs and exogenous ncRNAs in the regulation of these pathways. We focus on microRNAs (miRNAs), long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), and exogenous ncRNAs and their roles in regulating key signaling pathways such as the Wnt/β signaling pathway. β-catenin, PI3K/Akt, and TGF-β. We also discuss the potential of ncRNAs and exogenous ncRNAs as diagnostic and prognostic biomarkers for CRC, as well as their potential as therapeutic targets for CRC. Advances in ncRNA-based therapies present promising opportunities for the development of new therapies for CRC. A better understanding of the roles of ncRNAs and exogenous ncRNAs may lead to the development of new therapeutic strategies for this disease.